Rural treatment of COVID-19 patients with pirfenidone, nitazoxanide and colchicine. Case series - Iturbe Esquivel, Brandon; Meneses Calderón, José; Concepción Carrillo, Luis Edgar; Mendieta Zeron, Hugo (Monaldi Archives for Chest Disease, 2022)
Combined treatments against SARS-CoV-2 are emerging and some have taken into account the post-COVID-19 fibrosis. The aim of this survey was to report the experience of treating COVID-19 patients with pirfenidone, nitazoxanide (NTZ) and colchicine. It was a case series report of COVID-19 patients treated from December 2020 to March 2021, in a rural health center located in the State of Mexico, Mexico. 23 patients were included (mean age 44.5 ± 17.1 years), 12 women (mean age 45.9 ± 17.9 years) and 11 men (mean age 43 ± 16.9 years) with four deaths (17.39%). The evolution time was of 17.3 ± 6.7 days being the main symptoms fever (82.6%), myalgia (69.6%) and cough (65.2%). The main comorbidities were overweight/obesity 18 (78.26%), type 2 diabetes mellitus (T2DM) 4 (17.39%), Chronic obstructive pulmonary disease (COPD) 5 (21.73%) and systemic hypertension 2 (8.69%). Two patients were intubated and both died; in these cases, they refused to take NTZ until after three days the medical doctor had prescribed it for the first time. It can be concluded that implementing a mixed treatment with pirfenidone, NTZ and colchicine could improve the survival rate in ambulatory patients of low socioeconomic status.